Analisis Pengaruh Audit Committee terhadap Firm Value dan Firm Performance Melalui ESG Disclosure (Studi pada Perusahaan yang Terdaftar di Bursa Efek Indonesia Indeks Sri Kehati Periode 2018-2022) - Figosutansyah, Atev; Hersugondo, Hersugondo (Diponegoro Journal of Management, 2024)
ABSTRACT This study aims to analyze the effect of the Audit Committee on Firm Value and Firm Performance through ESG Disclosure in companies listed on the Sri Kehati Index BEI for the 2018-2022 period. This study uses quantitative data types with secondary data sources obtained through the financial statements of each company downloaded through Bloomberg, the official website of the Indonesia Stock Exchange (www.idx.co.id) and financial reports downloaded from each company's website. The number of samples used was 25 companies listed on the Sustainable and Responsible Investment (SRIKEHATI) index listed on the Indonesia Stock Exchange for the period 2018-2022. The analytical tool used in this research is the PLS structural equation model (SEM). The results of this study indicate that the Audit Committee has a significant positive effect on ESG Disclosure, the Audit Committee has a significant positive effect on Firm Value, the Audit Committee has a significant positive effect on Firm Performance, ESG Disclosure has no effect but is significant to Firm Value, and ESG Disclosure has a significant positive effect on Firm Performance.